Health protocol implementation with Scabies at Junior High School Kebumen during the COVID-19 pandemic - Adibah Zahra; Farindira Vesti Rahmasari; Gina Puspita; Kanti Ratnaningrum; Tri Wulandari Kesetyaningsih (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
Scabies is a skin disease that is very difficult to get rid of in Islamic boarding schools. Even with the implementation of a fairly strict health protocol during the COVID-19 pandemic, it has not been able to stop its spread. This study aimed to determine the relationship between the implementation of health protocols and scabies cases that occurred at the VIP-Al Huda Junior High School Kebumen during the COVID-19 pandemic. This was an analytic observational study with a case-control research design. The data was collected from December 2021 to February 2022. There were 100 male and female students in grades 7 and 8 who became the study's sample, consisting of 50 students in the case group and 50 students in the control group. Chi-square was used to analyze the data. The results reported that there is a relationship between adherence to the implementation of health protocols (OR 4.750; p 0.001) and scabies cases at the VIP Al-Huda Junior High School Kebumen during the COVID-19 pandemic. It was concluded that compliance with the implementation of health protocols related to scabies cases that occurred at the VIP Al-Huda Junior High School Kebumen during the COVID-19 pandemic.